Compressive fatigue and fracture toughness behavior of injectable, settable bone cements. (November 2015) - Harmata, Andrew J.; Uppuganti, Sasidhar; Granke, Mathilde; Guelcher, Scott A.; Nyman, Jeffry S.
Abstract: Bone grafts used to repair weight-bearing tibial plateau fractures often experience cyclic loading, and there is a need for bone graft substitutes that prevent failure of fixation and subsequent morbidity. However, the specific mechanical properties required for resorbable grafts to optimize structural compatibility with native bone have yet to be established. While quasi-static tests are utilized to assess weight-bearing ability, compressive strength alone is a poor indicator of in vivo performance. In the present study, we investigated the effects of interfacial bonding on material properties under conditions that re-capitulate the cyclic loading associated with weight-bearing fractures. Dynamic compressive fatigue properties of polyurethane (PUR) composites made with either unmodified (U-) or polycaprolactone surface-modified (PCL-) 45S5 bioactive glass (BG) particles were compared to a commercially available calcium sulfate and phosphate-based (CaS/P) bone cement at physiologically relevant stresses (5–30 MPa). Fatigue resistance of PCL–BG/polymer composite was superior to that of the U-BG/polymer composite and the CaS/P cement at higher stress levels for each of the fatigue failure criteria, related to modulus, creep, and maximum displacement, and was comparable to human trabecular bone. Steady state creep and damage accumulation occurred during the fatigue life of the PCL–BG/polymer and CaS/P cement, whereas creep of U-BG/polymer primarily occurred at a low number of loading cycles. From crack propagation testing, fracture toughness or resistance to crack growth was significantly higher for the PCL–BG composite than for the other materials. Finally, the fatigue and fracture toughness properties were intermediate between those of trabecular and cortical bone. These findings highlight the potential of PCL–BG/polyurethane composites as weight-bearing bone grafts. Graphical abstract: Highlights: Surface-modified bioglass composite had longer fatigue life than calcium-phosphate cement. Fatigue failure of composite and cement included both creep and damage accumulation. Steady state creep of cement at low stress occurred over higher strain range than composite. Crack initiation toughness was significantly higher for composite than for cement. PCL–BG/PUR composite is a potential synthetic bone graft for regions under dynamic loading.